Studying Osteoarthritis Pathogenesis in Mice. Issue 4 (21st September 2018) - Blease, Andrew; Das Neves Borges, Patricia; Curtinha, Marcia; Javaheri, Behzad; von Loga, Isabell S.; Parisi, Ida; Zarebska, Jadwiga; Pitsillides, Andrew; Vincent, Tonia L.; Potter, Paul K.
Abstract: With the increasing availability and complexity of mouse models of disease, either spontaneous or induced, there is a concomitant increase in their use in the analysis of pathogenesis. Among such diseases is osteoarthritis, a debilitating disease with few treatment options. While advances in our understanding of the pathogenesis of osteoarthritis has advanced through clinical investigations and genome‐wide association studies, there is still a large gap in our knowledge, hindering advances in therapy. Patient samples are available ex vivo, but these are generally in the very late stages of disease. However, with mice, we are able to induce disease at a defined time and track the progression in vivo and ex vivo, from inception to end stage, to delineate the processes involved in disease development. © 2018 by John Wiley & Sons, Inc.